Optimization of periodic synchronization of UAV's clock by differential phase method - A.I. Sulimov (Учёные записки Казанского университета: Серия Физико-математические науки)
The article considers the problem of designing a synchronized aerial wireless sensor network of unmanned aerial vehicles (UAVs) with centralized control by a master unit. A 10-ns synchronization precision must be ensured for all units within the aerial network in the time intervals of at least 100 s. To achieve it, the master unit periodically generates a synchronizing signal with two coherent sine tones of different frequencies that helps the slave UAVs to adjust their clocks. High-stability oven-controlled crystal quartz oscillators (OCXO) are used as onboard clocks for the UAVs.